Parallels between natural selection in the cold‐adapted crop‐wild relative Tripsacum dactyloides and artificial selection in temperate adapted maize. (26th June 2019) - Yan, Lang; Kenchanmane Raju, Sunil K.; Lai, Xianjun; Zhang, Yang; Dai, Xiuru; Rodriguez, Oscar; Mahboub, Samira; Roston, Rebecca L.; Schnable, James C.
Summary: Artificial selection has produced varieties of domesticated maize that thrive in temperate climates around the world. However, the direct progenitor of maize, teosinte, is indigenous only to a relatively small range of tropical and subtropical latitudes and grows poorly or not at all outside of this region. Tripsacum, a sister genus to maize and teosinte, is naturally endemic to the majority of areas in the western hemisphere where maize is cultivated. A full‐length reference transcriptome for Tripsacum dactyloides generated using long‐read Iso‐Seq data was used to characterize independent adaptation to temperate climates in this clade. Genes related to phospholipid biosynthesis, a critical component of cold acclimation in other cold‐adapted plant lineages, were enriched among those genes experiencing more rapid rates of protein sequence evolution in T. dactyloides . In contrast with previous studies of parallel selection, we find that there is a significant overlap between the genes that were targets of artificial selection during the adaptation of maize to temperate climates and those that were targets of natural selection in temperate‐adapted T. dactyloides . Genes related to growth, development, response to stimulus, signaling, and organelles were enriched in the set of genes identified as both targets of natural and artificial selection. Significance Statement: Corn was domesticated in Central America and is sensitive to cold temperatures, while its close relative, Eastern gamagrass, can survive the winter. We compared rates of protein sequence evolution across orthologous genes in seven grass species to identify genes involved in adapting gamagrass to life in the United States Corn Belt and found that the same genes were targets of artificial selection when new varieties of corn were developed to grow in temperate North America.